“Gut. The Inside Story of Our Body´s Most Underrated Organ.” By Giulia Enders - Gonzales Gil, Patricia (2015)
Short review of the most important and interesting sections of the popular science book that we strongly recommend: “Gut. The Inside Story of Our Body´s Most Underrated Organ”.